Análise dos atributos de escolha de companhia aérea pelo passageiro em voos domésticos no Brasil: proposição de um modelo - SANTOS FILHO, Nelson Marques dos (2015)
Catering is the expression employed for the industry that produces food and the delivery ready or semi-ready, as occurs in an airline providing food and beverage service while flying in an aircraft. In aviation this service is carried out by companies experienced in the industrialization of foods of varied types. But this was only possible with the development of commercial civil air transport after the Second World War. Serving food and beverages in flight has become a reality, catering to air travel mainly on long-distance and food-safe routes. There are no studies on the influence of catering on the attributes of airline choice by passengers and in face of these approaches, the research problem arose: "catering is a determining factor that influences passenger satisfaction for the choice of an airline in flights in Brazil? " The general objective of the research was to analyze and evaluate the influence of catering, that is, the provision of food and beverage service (A & B), in the decision of the passenger in relation to the choice of an airline for domestic flight in Brazil. The specific objectives of this study were: 1) to develop a theoretical framework that justifies the study; 2) make a survey of the attributes that interfere with the satisfaction of the passenger; 3) to propose a model that measures these attributes of choice in relation to the provision of services in an airline. The methodological procedures for this research were considered quali-quanti. The research was classified as exploratory, descriptive and explanatory. The first phase was exploratory, the second phase was descriptive and the third phase was explanatory. To support the second and third phase, a closed questionnaire with seven-point scale, based on the Likert scale, was developed and used in the Survey. The third phase was composed of an explanatory level research using the factors discovered in phase 2, in order to analyze the relationships between the constructs. The hypotheses tested were: H1 - The provision of quality services positively implies comfort in A & B in airlines; H2 - The provision of quality services positively implies the concept of low cost, improving the positive view of the airline customer. The results indicated that the exploratory factorial analysis (APE) obtained a KMO of 0.931, considered good, an explanation of the total variance of 75.25% and a solution with three factors: a. Provision of Quality Services; B. Comfort in A & B; w. Low cost. After AFE, a model submitted to confirmatory factorial analysis (AFC) was proposed, which confirmed the hypothesis of the study. The understanding of these factors and the creation of the PCPL model (an acronym for the representation of the positive correlations between "Quality Service Delivery - Comfort in A & B" and "Quality Service Delivery - Low cost") a model that makes it possible to choose a company that offers a variety of quality services and with a low cost transportation fare.